2018
DOI: 10.5334/gjgl.360
|View full text |Cite
|
Sign up to set email alerts
|

(Dis)agreement, polarity, and focus: Answering negative polar questions in Italian

Abstract: Among languages that employ specialized particles for answering polar questions, two major groups are known: Positive-Negative (P-N) and Agreement-Disagreement (A-D). English and Italian are examples of the former group, Japanese an example of the latter. It has occasionally been remarked in the literature that at least in some P-N languages a narrow focus in a negative polar question affects the choice of responding particles: namely, the answering pattern shifts to A-D. In the present contribution, this clai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In Italian, Servidio et al (2018) report an experimental investigation on an exceptional answering pattern that occurs when narrow focus is fronted in a question (i.e., in negative nuclear questions). Unlike the case for answers to negative total questions such as that in example 77a, where yes would be used for PD and no for NA, in negative nuclear questions such as example 77b, sì would be used for NA and no for PD.…”
Section: Disclosure Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…In Italian, Servidio et al (2018) report an experimental investigation on an exceptional answering pattern that occurs when narrow focus is fronted in a question (i.e., in negative nuclear questions). Unlike the case for answers to negative total questions such as that in example 77a, where yes would be used for PD and no for NA, in negative nuclear questions such as example 77b, sì would be used for NA and no for PD.…”
Section: Disclosure Statementmentioning
confidence: 99%
“…(adapted from Servidio et al 2018, pp. 6-7) Other strategies to express (positive) disagreement (i.e., for rejecting responses to negative antecedents) that have been described in the literature involve the use of special lexical particles (e.g., Romanian ba, German doch, French si, Scandinavian jo, Dutch jawel ), vowel lengthening and higher pitch tone on the no response particle (e.g., Italian; Servidio et al 2018), repetition of particles (e.g., Catalan and Russian;González-Fuente et al 2015), and rejection gestures (e.g., strong/repeated head nod, head tilt, strong/slight eyebrow raising, shrug; González-Fuente et al 2015, Li et al 2016). These studies have reported a combination of lexicosyntactic, prosodic, and gestural strategies for the rejection of negative assertions and questions.…”
Section: Disclosure Statementmentioning
confidence: 99%
“…Due to their prevalence in all languages, polar questions have received much attention in the syntactic research. A review of the literature has shown many studies that investigates polar (yes/no) questions) in many languages and some issues related to them such as English negative polar questions (Aksenovová, 2022); negative polar question types in English (Romero, Arnhold, Braun & Domaneschi, 2017); negative polar questions in English and Czech (Malá, 2007); polar questions in Seri (Marlett & Moser, 2000); negation, alternatives, and negative polar questions in American English (AnderBois, 2019); negative answers to polar questions in English (Park & Yang, 2022); (Dis) agreement, polarity, and focus in answers to negative polar questions in Italian (Servidio, Bocci & Bianchi, 2018); polar question forms expressing bias-evidence conflicts in Italian (Di Maro, Origlia, & Cutugno, 2021); the particle mica in Italian polar questions and attitudes in discourse (Frana, & Rawlins, 2019); affirming responses to polar questions in Russian conversation (Bolden, 2016); question bias and question concern in negative polar questions in Russian (Repp & Geist, 2022); the syntax of answers to polar questions in English and Swedish (Holmberg, 2013); new perspectives on bias in polar questions in Hungarian (Gyuris, 2017); what is and (isn't) asked with a (negative) polar question in Serbian? (Todorovic, 2022); intonation and its interfaces in Sardinian polar questions (del Mar Vanrell, Ballone, Schirru, & Prieto, 2014); the interpretation of responses to particles méi (yǒu) and bù in negative polar questions in Mandarin Chinese (Li, Borràs-Comes & Espinal, 2022); the syntax of polar questions and their answers in Taiwanese (Wu, 2016); embedded negative polar questions in Japanese (Goodhue & Shimoyama, 2022); two varieties of negative polar interrogatives in Japanese (Ito & Oshima, 2014); bias and prosody in Japanese negative polar questions (Ito, 2015); the anaphoric nature of particle responses to the polar questions in English and Korean (Kim, 2017); variations in answering negative polar questions in Korean (Kim, Nam & Kim, 2023); negation and polar question-answer clauses in South African sign language (Huddlestone, 2021); what negative polar questions can teach us about the in domain for Turkish sign language (Gokgoz, 2010); negative polar questions in Hong Kong sign language (Sze & Lee, 2022) and others.…”
Section: Introductionmentioning
confidence: 99%